SMEs inventive performance and profitability in the markets for technology - Padula, Giovanna (2021)
This paper studies the inventive performance and profitability of small and medium sized firms (SMEs) that are "technology specialists" compared to the inventive performance and profitability of SMEs that are instead vertically-integrated. In this paper perspective, "technology specialists" are firms that specialize upstream in generating inventions and trade those inventions in disembodied form with other firms, usually through licensing agreements. Instead, vertically-integrated firms are those firms that both generate inventions and commercialize products incorporating those inventions. We argue that technology specialists achieve a higher inventive performance than vertically-integrated firms, since they can accumulate deeper and broader inventive experience, whilst keeping a more flexible organizational structure. These firms display a lower profitability though, due to the imperfections inherent in invention market transactions and the lower bargaining power caused by the lack of commercialization assets. The theoretical framework is tested through a cross-industry investigation on a sample of European SMEs. Implications for the viability of being a technology specialist as a strategy and for the development of markets for technology are discussed.